Prevalence of Abomasum Nematode infection in Sheep from North of Iran - Hamzehali Tehrani, M; Shemshadi, B; Shayan, P; Shirali, S; Panahi, N (Journal of the Hellenic Veterinary Medical Society, 2024)
Abstract In many countries, small ruminants provide the primary source of human protein and play an important role in livestock production. Parasitic infections, especially gastrointestinal parasites, cause economic losses such as reduced fertility and milk production, damage to the leather industry, weight loss, treatment costs, and losses in severe infections. Thus, identifying and classifying these parasites, including the above cases, is essential for scientific research in any country. This study aimed to Prevalence of Abomasum Nematode infection in Sheep from North of Iran. In the present cross-sectional descriptive study, we have studied the prevalence of infection with abomasum nematodes in sheep in northern Iran from April 2020 to September 2021 in 2400 abomasum sheep slaughtered in industrial slaughterhouses in Gilan and Mazandaran provinces (1200 sheep from each province). With three age groups of below two years, two to four years, and above four years and gender segregation of hosts, after necropsy and preparation of sheep abomasal mucosa chip and isolation and segregation of samples, we studied the morphologic and morphometric characteristics of the samples. The actions were performed according to the taxonomic keys and using SPSS software V.16 and Paired Sample T-Test statistical test to determine the level of significance of the data (p <0.05) to classify and compare the obtained data and examine the ratio. The sex of the host was determined by the age of the animal and the prevalence of the parasite at the mentioned ages. The present study results and comparison of the prevalence of infection in Gilan and Mazandaran provinces showed that Marshallagia marshalli had the highest prevalence of 94.6% and 91.9% in Mazandaran and Gilan province, respectively. The prevalence of Ostertagia circumcincta was 87.2% and 77.2% in Gilan and Mazandaran provinces. The prevalence of Ostertagia occidentalis was 86.9% in Gilan province and 78% in Mazandaran province, while the prevalence of Parabronema skrjabini was 86.6% in Gilan province and 61.2% in Mazandaran province. The prevalence of Haemonchus contortus was 66.8% and 60.5% in Gilan and Mazandaran, the lowest prevalence in these two provinces. The present study results showed the importance of combating the spread of parasitic infections with strategic treatment methods and biological control of these parasites. Also, various reports of drug resistance in abomasal nematodes should be emphasized more and more by competent bodies. Keywords: Abomasum, Nematodes, North of Iran, Parasitic infections, Sheep.